On Orthogonal Coupled Fixed Point Results with an Application - Gunaseelan Mani; Arul Joseph Gnanaprakasam; Khalil Javed; Santosh Kumar (Journal of Function Spaces)
In this manuscript, owing to the concept of orthogonal coupled contraction mappings type I and II, we prove coupled fixed point theorem in orthogonal metric spaces. In order to strengthen our main results, a suitable example is presented. Moreover, the results we obtained supplement and improve previous research findings. A fruitful application is also supplied to endorse our outcomes.